2019
DOI: 10.1111/tmi.13218
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for causal links between education and maternal and child health: systematic review

Abstract: Objective Numerous studies have documented an inverse association between years of schooling attained, particularly by women, and reduced maternal, infant and child mortality. However, if factors affecting educational attainment — many of which are unobservable, e.g. motivation and genetic endowment — also affect the likelihood of engaging in behaviours that enhance health, then assumed effects of schooling will be inflated in analyses that do not address this endogeneity. This systematic review a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
103
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(112 citation statements)
references
References 66 publications
3
103
0
6
Order By: Relevance
“…India's older population is particularly economically and socially vulnerable due to high rates of illiteracy and economic dependency (Bloom et al 2010). In this context, investments in children's education may be advantageous not only for the health of those individuals themselves (Grossman 1975;Link and Phelan 1995;Lleras-Muney 2005;Baker et al 2011;Berkman et al 2014;De Neve et al 2015) and for their own children (Gakidou et al 2010;Karlsson et al 2019;Mensch et al 2019), but also for the older generations (Zimmer et al 2007;Torssander 2013).…”
Section: Introductionmentioning
confidence: 99%
“…India's older population is particularly economically and socially vulnerable due to high rates of illiteracy and economic dependency (Bloom et al 2010). In this context, investments in children's education may be advantageous not only for the health of those individuals themselves (Grossman 1975;Link and Phelan 1995;Lleras-Muney 2005;Baker et al 2011;Berkman et al 2014;De Neve et al 2015) and for their own children (Gakidou et al 2010;Karlsson et al 2019;Mensch et al 2019), but also for the older generations (Zimmer et al 2007;Torssander 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although this finding appears counterintuitive, a growing literature suggests mixed child health returns to additional years of maternal schooling [35][36][37][38]. A recent systematic review examined evidence for a causal link between maternal education and child health and found that parental schooling may play a more muted role in parents' decisions about whether and how much to invest in their children's health than previously suggested [39]. Moreover, even well-educated parents seeking to correct common health risks in their children may lack access to high quality primary healthcare services or face high out-of-pocket expenditures [40].…”
Section: Discussionmentioning
confidence: 98%
“…The higher educational level of mothers, together with their better intellectual capacities, help in health choices, increase the understanding and use of information and improve the perception of health problems [45]. They also invest in more health-beneficial behaviors, both at the individual and child levels, showing better adherence to health recommendations in terms of nutrition, exercise and reduction of harmful habits [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%